Herbal remedies and medicine; introducing some Iranian plants - Rahmati Roodsari, Mohammad; Zamanian-Azodi, Mona; Salimpour, Fahimeh (Archives of Advances in Biosciences, 2013)
The overall goal of this review is to discuss the potential efficacy of herbal treatments. Plants are considered among the main sources of biologically active chemicals. Plant based drugs usage in our past decay became very renowned due to their fewer side effects and being less expensive than chemical ones. Recently, more abrupt tendency in this field has been increased. Furthermore, advances in molecular and cellular determinations revealed effective properties of these herbal components. Some plants extracts have shown multi-functional properties such as anti-oxidant, anti-amyloid, antimicrobial, and anti-inflammatory; further studies, besides, are required for detailed chemical characterization and more extensive biological evaluation of the most active ingredients. In summary, herbals can be considered as novel therapeutic approach against wide range of diseases. This review article draws the attention to some species of plants possessing biological activities on human health.